2007
DOI: 10.1007/s10286-006-0395-7
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic nervous system at high altitude

Abstract: IntroductionHigh altitude places are amongst the most inhospitable on earth. According to WHO [70] in 1966 there were approximately 140 million people living at altitudes over 2,500 m and there are several areas of permanent habitation at over 4,000 m. These are in three main regions of the world: the Andes of South America, the highlands of Eastern Africa, and the Himalayas of South-Central Asia. This review is concerned with the effects of the altitude on visitors and the ways by which the permanent high al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 66 publications
7
126
0
7
Order By: Relevance
“…The other way is through stimulation of pulmonary arterial baroreceptors in order to reduce the pulmonary hypertension elicited by the hypoxic stimulus. 41 As mentioned above, this sympathetic activation is reflected in changes in some HRV parameters under HH. An inverse relationship between sympathetic nerve activity and arterial SpO 2 in subjects with and without history of high altitude pulmonary oedema has been observed.…”
Section: Correlation Between Hrv Measurements In Normoxia and Spo 2 Imentioning
confidence: 84%
“…The other way is through stimulation of pulmonary arterial baroreceptors in order to reduce the pulmonary hypertension elicited by the hypoxic stimulus. 41 As mentioned above, this sympathetic activation is reflected in changes in some HRV parameters under HH. An inverse relationship between sympathetic nerve activity and arterial SpO 2 in subjects with and without history of high altitude pulmonary oedema has been observed.…”
Section: Correlation Between Hrv Measurements In Normoxia and Spo 2 Imentioning
confidence: 84%
“…This exaggerated BP rise could be a consequence of altitude‐induced reflex activation. We previously described that during exercise the ventilatory equivalents for oxygen and CO 2 were both higher at altitude compared to sea level,2 likely as a consequence of augmented peripheral chemoreflex input6, 22 and fluid accumulation along the alveolar capillary membrane 23…”
Section: Discussionmentioning
confidence: 99%
“…In previous articles, we demonstrated that acute exposure to high‐altitude hypobaric hypoxia induces a blood pressure (BP) rise in subjects with hypertension, both at rest over the 24 hours and during exercise,1, 2, 3 likely through chemoreflex‐induced sympathetic activation 4, 5, 6. Moreover, we also showed that the combination treatment with telmisartan and sustained‐release formulation of nifedipine gastrointestinal therapeutic system formulation (GITS) is able to lower BP levels during exercise not only at sea level but also at high altitude, as compared with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…The reductions in HR in the T. violacea -treated andcaptopril treated rats may also be partly due the animals becoming better accustomed to the small space, being more relaxed, and consequently, reducing sympathetic nervous system activation, which normally would increase HR and BP, as part of the 'fight', 'fright' or 'flight' response (Kurtz et al, 2005;Freeman et al, 2006;Fox et al, 2007;Hainsworth et al, 2007;McCorry, 2007;Reil & Bohm, 2007;Craven, 2008).…”
Section: Blood Pressure and Heart Ratementioning
confidence: 99%